When Issue Salience Affects Adjudication: Evidence from Swiss Asylum Appeal Decisions. Issue 1 (13th May 2021) - Spirig, Judith
Abstract: Immigration is a top concern among citizens across the globe. Research shows that the salience of immigration shapes voters' political behavior, but little is known about whether it influences judicial behavior. This article theorizes that variation in issue salience influences judges' behavior when there is a clear connection between the legal and a generally salient, politicized issue. I test this argument drawing on all Swiss asylum appeal decisions reached between 2007 and 2015. I find that higher asylum salience leads judges to decide otherwise similar asylum appeals less favorably. This effect is not restricted to judges affiliated with anti‐immigrant parties, unlikely to be driven by accountability pressures, and strongest for those topics known to drive anti‐immigrant sentiment in the general public. Together, these findings raise concerns that issue salience threatens the consistency of judicial decisions.